2020
DOI: 10.3390/met10091266
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Tensile Strength and Deformation of Diffusion Bonding Joint for Inconel 718 Using Deep Neural Network

Abstract: Due to the acceptable high-temperature deformation resistance of Inconel 718, its welding parameters such as bonding temperature and pressure are inevitably higher than those of general metals. As a result of the existing punitive processing environment, it is essential to control the deformation of parts while ensuring the bonding performance. In this research, diffusion bonding experiments based on the Taguchi method (TM) are conducted, and the uniaxial tensile strength and deformation ratio of the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…However, it requires extracting both amplitude and phasing characteristics during detection. For most nonlinear ultrasonic methods, including that in Ref [ 15 , 16 , 17 , 18 , 19 ], the excitation signal is a tone burst wave, which makes it difficult to extract the echo on the bond interface. Compared with the previous methods, the nonlinear ultrasonic C-scan imaging proposed in this work can easily obtain the echo on the bond interface and only needs simple signal processing to extract the nonlinear parameter and to form the C-can image.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it requires extracting both amplitude and phasing characteristics during detection. For most nonlinear ultrasonic methods, including that in Ref [ 15 , 16 , 17 , 18 , 19 ], the excitation signal is a tone burst wave, which makes it difficult to extract the echo on the bond interface. Compared with the previous methods, the nonlinear ultrasonic C-scan imaging proposed in this work can easily obtain the echo on the bond interface and only needs simple signal processing to extract the nonlinear parameter and to form the C-can image.…”
Section: Discussionmentioning
confidence: 99%
“…This method is theoretically not limited by the detection frequency and has higher detection sensitivity to small defects, especially when contact-type defects exist, and significant nonlinear components will appear in the received signal [ 15 , 16 ]. Studies have shown that linear ultrasound is more sensitive to macro-sized defects, and for contact-type defects, the linear ultrasound echo is weak, but the nonlinear response is strong [ 17 , 18 , 19 ]. However, there are currently few studies on the use of nonlinear ultrasound methods in pulse-echo mode to detect contact-type defects in diffusion-bonded joints.…”
Section: Introductionmentioning
confidence: 99%
“…Olazagoitia et al [15] showed that artificial neural networks can be used to directly identify the parameters of a tire model for a real test without iterative fittings or initial iteration point definitions without using complex cost functions. Mei et al [16] used the deep neural network model to accurately characterize the nonlinear relationship between the parameters of the Inconel 718 bonding process and bonding performance. Hijazi et al [17] used artificial neural networks modeling to predict the residual stress of aluminum panels using multiple site damage, showing that it can predict with high accuracy the residual strength for all materials and constructions considered in the study.…”
Section: Introductionmentioning
confidence: 99%